Study of plant oil and its ageing effect on system and rheological performance - W.B., Wan Nik; K.H., Ku Bulat; H.B., Senin; N.A., Ali; Rahman, Md. Mokhlesur; F.N., Ani (Asian Network for Scientific Information, 2007)
The effects of oil ageing on hydraulic system efficiency and oil rheological performance were studied. The various physical and chemical properties of fresh and aged oils were studied by determining total acid value, iodine value and density. The variation of oil functional group was analyzed by FTIR. The rheological behavior i.e., variation of viscosity with time, temperature and shear rate was studied using Brookfield viscometer. An attempt was made to establish the relationship between variation of viscosity and time of fresh and aged oil. The hydraulic performance has been investigated by determining system volumetric and mechanical efficiencies. The results show that the volumetric efficiency increases with ageing period while mechanical efficiency decreases when the oil ageing time increases.